High neuropilin and tolloid‐like 1 expression associated with metastasis and poor survival in epithelial ovarian cancer via regulation of actin cytoskeleton. Issue 16 (8th July 2020) - Xu, Yunzhao; Wang, Wei; Chen, Jinling; Mao, Haixia; Liu, Yuanlin; Gu, Shuting; Liu, Qinqin; Xi, Qinghua; Shi, Wenyu
Abstract: Abnormal expression of neuropilin and tolloid‐like 1 (NETO1) has been detected in some human carcinomas. However, the expression of NETO1 and the underlying mechanism in epithelial ovarian cancer (EOC) remain unknown. In this study, we found that a higher NETO1 expression in EOC tissue samples compared to normal ovarian tissue samples was significantly correlated with worse overall survival. Additionally, Cox regression analysis suggested that NETO 1 was independently associated with overall survival. NETO1 overexpression enhanced the EOC cells' migration and invasion capability in vitro via regulation of actin cytoskeleton. Mechanistically, silencing NETO1 reduced the expression of β‐tubulin, F‐actin and KIF2A. In conclusion, our results demonstrated the critical role of NETO1 in EOC invasion, and therapies aimed at inhibiting its expression or activity might significantly control EOC growth, invasion and metastatic dissemination.